National Food Security Act: A Relook - Kaiser, Zara Fathima (Christ University Law Journal, 2021)
It has been four years since the National Food Security Act, 2013 (NFSA) was passed, ample time for us to assess its impact on the food insecurity in India. The Act was initiated as an ambitious attempt to provide food security through a life-cycle approach, but over the years it has remained restricted to merely converting four schemes into legal entitlements. It has lost sight of its ultimate goal of providing „food security‟ and remains largely over occupied by food distribution. Additionally, core aspects of food production and management have been placed under schedule III, to be progressively realized, in other words "not imperative". The present paper shall critically analyze the concept of food security against the national Act. An attempt shall be made at highlighting the lacunae within the provisions of the Act, implementation gaps and operational inadequacies. Moreover, the interaction between the national law and the individual state rules and the impact of diverse state-specific factors on rule-making and ground-level implementation shall also be considered. The paper introduces the concept of food security and gives an overview of the NFSA. It also critically analyzes the provisions of the Act and highlights the gaps in food security therein. The paper concludes with recommendations as to how food security can be implemented in an effective way.